The Failure of Private Regulation: Elite Control and Market Crises in the Manhattan Banking Industry. (March 2013) - Yue, Lori Qingyuan; Luo, Jiao; Ingram, Paul
In this paper, we develop an account of the failure of private market-governance institutions to maintain market order by highlighting how control of their distributional function by powerful elites limits their regulatory capacity. We examine the New York Clearing House Association (NYCHA), a private market-governance institution among commercial banks in Manhattan that operated from 1853 to 1913. We find that the NYCHA, founded to achieve coordinating benefits among banks and to limit the effect of financial panics, evolved at the turn of the twentieth century into a device for large, elite market players to promote their own interests to the disadvantage of rival groups that were not members. Elites prevented the rest of the market from having equal opportunities to participate in emergency loan programs during bank panics. The elites' control not only worsened the condition of the rest of the market by allowing non-member banks to fail; it also diminished the influence of the NYCHA and escalated market crises as bank failures spread to member banks. As a result, crises developed to an extent that exceeded the control of the NYCHA and ended up hurting even elites' own interests. This paper suggests that institutional stability rests on a deliberate balance of interests between different market sectors and that, without such a balance, the distributional function of market-governance institutions plants the seeds of institutional destruction.